Diamondoid hydrocarbon ratios as indicators of biodegradation in Australian crude oils - Grice, Kliti; Alexander, Robert; Kagi, Robert (Elsevier Science, 2000)
The effect of biodegradation on diamondoid distributions in petroleum has been investigated on a series of crude oils reservoired in two Australian sedimentary basins, the Gippsland Basin and the Carnarvon Basin. The ratio of methylada-mantanes to adamantane rises with increasing biodegradation. Signicant changes in the ratio occur at extreme levels, indicating that diamondoids can be indicators of petroleum biodegradation especially when most other hydrocarbons have been removed. The methyladamantane/ adamantane ratio can also be used to assess the composition of crude oils that are comprised of a mixture of severely biodegraded and non-biodegraded oil.